(untitled) (Fiep Bulletin - online, 2012)
Education is the bases that comprehend the formative processes. Stimulates the development to enjoy of autonomy. An education that assumes the experience of adventure with the children certainly will provide through ludic the facility of imaginary, memory creating conditions for learning experiences in the word around them. The problem is, in regard to the social and cultural development of children from violent communities in the city of Rio de Janeiro in their leisure time experienced the non-formality in their childish games. The study is justified because it is extremely importance for parents, teachers and authorities that deal directly or indirectly with children such transgressions as a way if living symbolic imagination of the comic book often read in the school. The goal is to understand the meanings of children of 5º and 6º grade of a school community of Cidade de Deus in Rio de Janeiro manifest on their walks in the forest. The qualitative, interpretative research, interviewed 10 boys between 11 and 15 years old. It is concluded that the adventure presupposes a break with the family or social world being point of departure for a strange world. The adventure activities have great significance in the process of child development. In the sense, see them venturing in nature presents us with a privileged place of discovery of their potential. The meaning of adventure has previous knowledge of experience, which is a break from everyday life, something different. Children have different feelings, according to the place where it is practiced their adventure.